Hamemayu Hayuning Bawono Dalam Ekoteologi Keseimbangan Pada Surat Ar-Rahman 6-10 - Hutama, Lanang (Indonesian Journal of Islamic Theology and Philosophy, 2025)
Abstract This study examines the relationship between the Javanese philosophy of Hamemayu Hayuning Bawono and the concept of balance (al-mīzān) in Islamic eco-theology as reflected in Surah Ar-Rahman, verses 6–10. Using a qualitative approach based on library research through content and comparative analysis, this study explores how Islamic teachings and Javanese wisdom provide guidance in maintaining environmental balance. The results show a harmony between the two in affirming human responsibility to care for nature, maintain the balance of life, and avoid excessive and wasteful attitudes. The synthesis of these values produces an ethical framework relevant to modern environmental issues such as waste management and ecological degradation, particularly in Yogyakarta. The novelty of this research lies in the revelation of the conceptual relationship between Hamemayu Hayuning Bawono and al-mīzān in shaping a society's character based on spiritual and cultural values. This research contributes to the development of a new paradigm of Islamic eco-theology integrated with local philosophy, while strengthening environmental conservation efforts through moral, religious, and cultural approaches. Keywords: Balance Principle; Ecotheology; Environmental Ethics; Javanese Philosophy; Quran